Development of A Smash Drill Training Model To Improve Smash Accuracy In Extracurricular Volleyball Students In High School/Vocational School (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2025)
This study aims to develop a straight and cross smash drill training model using root obstacles to improve smash accuracy in extracurricular volleyball students. This study uses the Research and Development (R&D) method with a development model referring to the Borg & Gall 7-step model, namely: (1) Preliminary study, (2) Planning, (3) Initial draft design, (4) Initial draft validation and revision, (5) Product trial (small-scale trial/revision, large-scale trial/revision), (6) Final product, (7) Effectiveness test. The research subjects were ten volleyball extracurricular students at SMA Negeri 10 Purworejo Regency and ten students of SMK Vip Ma'arif Nu 1 Kemiri. The validation results showed that the developed training model was declared "valid" with a score of 0.825 from the material expert and 0.75 from the media expert's score. Then the results of expert validation in small-scale trials got a score of 0.818 with the criteria of "valid", then for the results of expert validation in large-scale trials got a score of 0.85 with the criteria of "very high and valid". The effectiveness test got a p-value smaller than 0.05, namely 0.00